The impact of active learning and learning style on blended learning: Insights from higher education students - Fazilah Razali; Tajularipin Sulaiman; Ahmad Fauzi Mohd Ayub; Noraziela Abdul Majid (International Journal of Evaluation and Research in Education (IJERE), 2023)
Blended learning is a progressive teaching technique combining online and face-to-face instruction to encourage active learning and improve academic achievement. However, various problems, such as different attitudes and learning styles between educators and students, influenced the implementation of blended learning effectively. Therefore, there is a need to identify the factors that impact blended learning to improve students’ performances and enhance blended learning. In this study, the proposed framework examines the mediation effect of active learning on the relationship between learning styles and accessibility of learning through blended learning. The study sample consisted of undergraduate students from Universiti Putra Malaysia. In addition, this study also utilized a random sampling method. In total, 224 responses were collected and analyzed using a partial least square structural equation modeling (PLS-SEM). The findings revealed that active learning fully mediated the relationship between learning style and blended learning. Active learning also mediated the relationship between accessibility and blended learning with complementary mediation. Moreover, this study offers several practical suggestions for essential parties, including the government and the education sector, to optimize blended learning approaches in Malaysia.